Estudo da ampliação de escala na produção de biomassa de Rhodotorula sp. CNPAT02 em processo batelada para obtenção de carotenóides - Castelo Branco, Leise Soares (2010)
The genus of yeast Rhodotorula are known to accumulate considerable amounts of carotenoids, which are important natural pigments found in foods and widely distributed in plants and microorganisms. In addition to human consumption, R. glutinis is used to feed chickens to increase body fat and to improve appearance and nutritional sensory properties of meat. Studies report that β-carotene is widely used to prevent various types of cancer due of its antioxidant properties. The objectives of this study are to scale up the fermentation to a bench-scale bioreactor to obtain carotenoids and study the spray-drying process of cells of Rhodotorula sp. CNPAT02. The yeast was grown in a 14 litter stirred tank fermentor, and the biomass obtained was concentrated by centrifugation and then spray dried. 50 mL of culture medium were prepared containing the following concentrations: (g.L-1): glucose, 25; yeast extract, 3.57; K2HPO4, 2.0; KH2PO4, 2.0; MgSO4.7H2O, 0.1 and pH 6.0. The medium was distributed in 500mL Erlenmeyer flasks and inoculated from a culture with a volume necessary to obtain an inoculum of about 0.1g dry mass/L. The medium was then incubated at 30°C for 36 hours in orbital shaker at 150 rpm. The culture was then transferred to a 2L flask containing 450mL of sterile medium incubated for 24 hours. The culture medium containing 500 mL was used to inoculate the fermentor where cell growth continued for 120 hours under an aeration of 1.0vvm-1. Samples were taken from the fermentor at regular intervals of 12h for determination of biomass, sugars, carotenoids and color. At the end of the 120h, the fermentation medium was centrifuged for 10 min at 11800g (8000 rpm). Aliquots of concentrated cells were suspended in distilled water before drying. From the dry sample, cell viability, the water activity, moisture, color and instrumental color were assessed. Carotenoids were extracted and quantified by using organic solvents. After 120 hours of fermentation the concentration obtained was 11.85 ± 1.10 g.L-1 of biomass and roductivity 2.45 g.L-1h-1 of carotenoids.